Endometritis in the bitch: Immunohistochemical localization of cyclooxygenase 2 - García Mitacek, María Carla (2020)
Background: In several mammals, subfertility or infertility associated with endometritis was reported. Although there have been studies about endometritis in bitches, the pathophysiological mechanisms are not completely known. Aim: This study aimed to evaluate the immunohistochemical expression of Cyclooxygenase 2 (COX2) in clinically healthy bitches with normal uterine tissue and bitches with endometritis. Methods: Forty-eight mixed breed bitches in diestrus were used. Uterine biopsies were collected for diagnosis [normal endometrium (n = 15; NE), cystic endometrial hyperplasia (n = 1), atrophy (n= 2), acute endometritis (n = 9; AE), subacute endometritis (n = 7; SE), and chronic endometritis (n = 14; CE)]. Immunostaining and quantification of positively stained cells was performed on full-thickness uterine biopsies. Data were analyzed by the GLIMMIX procedure of SAS. Results: COX2 immunostaining was scattered and restricted to cells in the stroma in bitches with NE. However, in bitches with endometritis, strong staining was observed in the luminal epithelium, glandular epithelium, and stromal cells. Staining was also observed in inflammatory cells localized in the stroma as well as inside of the glands. The percentage of COX2 positive stromal cells in bitches with AE, SE, and CE was significantly higher compared with NE (p < 0.005). In addition, the percentage of COX2 positive stromal cells in bitches with SE, and CE was significantly lower compared with AE (p < 0.003). Conclusion: COX2 could be involved in the pathophysiological mechanisms producing endometritis without the presence of cystic endometrial hyperplasia in bitches. However, further researches on this topic are required.